Treatise on process metallurgy; vol.3 - Guthrie, Roderick; McLean, Alexander; Seetharaman, Sridhar; Sohn, H. Y. (Cambridge : Elsevier, 2024)
This treatise provides a comprehensive overview of industrial processes in the field of process metallurgy. Edited by experts from prestigious institutions, it covers a broad range of topics including the metallurgy of iron and steelmaking, extraction of nonferrous metals, and the development of new technologies for material processing. The book also discusses the recovery of useful products from metallurgical waste and advancements in solar-grade silicon production. It targets researchers, practitioners, and students in metallurgy and materials science, aiming to disseminate cutting-edge research and practical developments in the field. This volume serves as a valuable resource for understanding both theoretical principles and practical applications in industrial metallurgy.
Includes index
Keywords: Metallurgy; Nonferrous metals